Social Marketing sebagai Katalisator Inovasi Pemasaran Sektor Publik untuk Dampak Sosial Berkelanjutan - Nisa Nur Amanda; Annisa Putri Jufani; Mely Nur Ratman; Suci Oktapia; Wahjoe Pangestoeti (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
Social marketing is a strategic approach that is increasingly applied in public sector marketing to encourage behavioral change and create sustainable social impacts. Unlike commercial marketing, social marketing focuses on public interests by integrating marketing principles to address various social issues. This article aims to examine the role of social marketing as a catalyst for innovation in public sector marketing, particularly in promoting behavioral change and generating sustainable social outcomes. The research method employed is a literature review by analyzing relevant scholarly sources. The findings indicate that well-designed social marketing initiatives can enhance public awareness, participation, and engagement in addressing public issues such as health, environmental sustainability, and social welfare. In addition, social marketing contributes to strengthening public trust in government institutions and supporting the sustainability of public policies. Therefore, social marketing can be considered an innovative and effective instrument in achieving sustainable social development goals within the public sector.